Marketing of Services in Open Distance Learning: A Feedback Study on Dr.BRAOU - Anand Pawar, I. (Indian Journal of Marketing, 2008)
The present paper on ’Marketing of Services in Open Distance Learning (ODL) is a micro level study on Dr. BRAOU students’. ODL System in India still struggling for recognition and well acceptance, even after 45 years of its existence. ODL contribution to the Higher Education System is about 32 per cent whereas; Conventional Education is only 8 per cent. At present there are 14 single mode Open Universities and 117 Distance Education Centres (DECs) in India catering to the needs of higher learning with specialized services. But unfortunately, ODL system has not been recognized or received either on par with conventional education or DECs of Conventional Universities. It is in this context, the present study is aimed at: (a) to know the learner perception towards ODL system; (b) to strengthen and satisfy the customer (learner) through after sale (admission) services. To conclude, 41 per cent of respondents opined that the services of BRAOU are not at all satisfactory, 40 per cent satisfactory and only 19 per cent highly satisfied. Out of 41 per cent, 65 per cent of issues related to examination services, 25 per cent towards learner support services and 10 per cent regarding material production including other services. Further, this study also suggested that: (a) ODL institutions should improve after admission services through strengthening communication system,(b) counter services, (c) staff training for treating and responding learners properly and respectively, etc.